Hispanic Perspective on Current Communication Research (2014-2019) - Piñeiro-Naval, Valeriano; Morais, Ricardo; Pedro Baptista, João (Revista General de Información y Documentación, 2021)
With regard to the evaluation of the curricular merits of researchers, the growing institutional demands have had a great impact on both the volume of works published by communication journals, and on the publication patterns of the authors. From this point of view, the goal of our study is to characterize this production in a systematic, objective and quantitative way. To do this, a content analysis was carried out on a probabilistic sample of 2103 articles, belonging to the 7 Hispanic journals with the greatest impact during the 2014-2019 six-year period, and indexed in the SCImago Journal Rank repository. The results obtained endorse the constant annual increase in the number of publications, as well as a slight decrease in their impact in recent years. In the same way, multiple authorship has become a modal practice that reflects, in turn, a greater role of male researchers compared to female among the first authors of manuscripts, that are frequently translated into English to stimulate their internationalization. Regarding the affiliation of the authors, it is linked to the Spanish university environment (with Madrid and Barcelona as epicenters) and to multiple disciplines. Finally, and despite the existence of R&D&I programs at various levels (local, regional, national and international), there is insufficient extra funding for scientific activity. In this sense, it is also confirmed that the impact of research increases as financial support increases, hence the convenience of having, or taking part of, funded projects.
Keywords: Research; communication; Academic papers; Scientific journals; SCImago Journal Rank; Spain; Latin-America